2007
DOI: 10.1177/0149206307308588
|View full text |Cite
|
Sign up to set email alerts
|

Executive Compensation: A Multidisciplinary Review of Recent Developments

Abstract: The failure to document a consistent and robust relationship between executive pay and firm performance has frustrated scholars and practitioners for over three quarters of a century. Although recent compensation research has revealed alternative theoretical frameworks and findings that hold the potential to significantly improve our understanding of executive compensation, to date this diverse literature lacks theoretical integration. Accordingly, we develop a framework to organize and review these recent fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
435
2
29

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 429 publications
(475 citation statements)
references
References 146 publications
9
435
2
29
Order By: Relevance
“…Some studies stated that CEO pay is not always beneficial. Devers et al (2007) has reported that the stock-based pay may encourage CEO to engage in negative behavior or so called fraud. Since there is a heavy usage of stock-based pay which provides CEOs with perverse incentives to maximize their private wealth, then CEO may have more advantage on boosting their accounting earning which is sometimes can be illegal.…”
Section: Dependent and Independent Variables Ceo Pay And Firm Performmentioning
confidence: 99%
“…Some studies stated that CEO pay is not always beneficial. Devers et al (2007) has reported that the stock-based pay may encourage CEO to engage in negative behavior or so called fraud. Since there is a heavy usage of stock-based pay which provides CEOs with perverse incentives to maximize their private wealth, then CEO may have more advantage on boosting their accounting earning which is sometimes can be illegal.…”
Section: Dependent and Independent Variables Ceo Pay And Firm Performmentioning
confidence: 99%
“…The executive compensation literature has since taken two routes to test the notion contained in Jensen and Meckling's agency theory (Devers et al 2007). First, several studies have been conducted to assess behavioral and performance effects of performance-related pay.…”
Section: Introductionmentioning
confidence: 99%
“…First, as of today, executive compensation practices have been widely investigated, in particular in the US and somewhat less so in the UK. However, there still is little systematic evidence on the pay packages received by top managers in other countries (Barkema and Gomez-Mejia 1998;Devers et al 2007). Results of these US-UK studies are translated into policy prescriptions throughout the world, largely disregarding local conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Researcher showed that the level of executive compensation mainly depends on company properties as well as on personal characteristics of the manager. Firm size (Fahlenbrach 2009;Renner et al 2002) firm performance (Antle and Smith 1986;Bebchuk and Fried 2006;Devers et al 2007), and a firm's ownership structure (Thomsen and Pedersen 2000;Chowdhury and Wang 2009) are company properties that researchers identified as drivers of executive compensation levels. Managers' tenure (Hill and Phan 1991) and gender (Kulich et al 2011;Renner et al 2002), on the other hand, are personal characteristics that influence managers' compensation levels directly or as moderating effects, e.g., through affecting labor market mobility and search firms' preferences (Dreher et al 2011).…”
Section: Literature Overview Theoretical Background and Hypothesesmentioning
confidence: 99%
“…As financial characteristics, we use LEVERAGE (quotient of total debt to total assets) as a proxy for the company's capital structure (Shaw and Zhang 2010) as well as the variable RISK (standard deviation of the operating performance over the focal and the 2 preceding years divided by their mean-winsorized to guard from outliers) to depict firm risk. We incorporate an accounting-based as well as a stock-based measure for firm performance (Kulich et al 2011;Adams and Ferreira 2009), i.e., the company's ROE and TOBIN'S Q, respectively, to control for their effects on executive compensation (Antle and Smith 1986;Bebchuk and Fried 2006;Devers et al 2007).…”
Section: Variablesmentioning
confidence: 99%